Efficacy of cinnamon in reducing anthropometric measurements in individuals with type 2 diabetes: a clinical trial - José Cláudio Garcia Lira Neto; Márcio Flávio Moura de Araújo; Jardeliny Corrêa da Penha; Maria Augusta Rocha Bezerra; Bruna Karen Cavalcante Fernandes; Thatiana Araújo Maranhão; José Wicto Pereira Borges; Marta Maria Coêlho Damasceno (Revista Brasileira de Enfermagem, 2025)
ABSTRACT Objectives: to evaluate the effectiveness of cinnamon (Cinnamomum verum) in reducing anthropometric measurements in individuals with type 2 diabetes. Methods: a randomized, triple-blind, placebo-controlled clinical trial was conducted with 140 participants, divided into an experimental group (n = 71) and a control group (n = 69). The experimental group consumed 3 g/day of encapsulated cinnamon for 90 days. Anthropometric variables were measured at baseline and at the end of the study, with intra-group comparisons performed using a paired t-test. Results: the majority of participants were women (69.2%) with a mean age of 61 years. Reductions were observed in weight (-0.8 kg, p =0.11), body mass index (-0.36 kg/m2, p =0.16), body adiposity index (-1.02%, p =0.38), waist circumference (-3.97 cm, p =0.67), neck circumference (-0.45 cm, p = 0.68), and hip circumference (-1.83 cm, p =0.49), none of which were statistically significant (p > 0.05). Conclusions: cinnamon supplementation resulted in reductions in anthropometric measurements compared to placebo, but these differences were not statistically significant.